PENGARUH PENERAPAN MODEL PEMBELAJARAN TIPE QUESTION STUDENTS HAVE (QSH) TERHADAP HASIL BELAJAR IPS SISWA KELAS VII DI SMPN 17 PADANG - Yunita, Elpina - (Pendidikan Sejarah, 2014)
The background of this research is about learning process of IPS (history) that is still from the teachersâ material, the students only listen the teacher in front of class. Otherwise, there are not least variation media and strategy in teaching process in order to the students can understand and active in the class. This case caused low score of IPS lesson at class VII SMPN 17 Padang year 2013/2014. One of strategy can improve the studentsâ score which applying learning model for Question Students Have type where the purpose of the research is to know the studentsâ score with applying learning model for Question Students Have type is more good method than the studentsâ score by using speak up method in the class VII SMPN 17 Padang.This research is experiment research, this research is done in SMPN 17 Padang mount April â May two semester year 2013/2014. The population of the research is all of the students at VII SMPN 17 Padang. Take of sampling is Total Sampling where is VII1 as experiment class and VII2 as control class. The result of the research show that the studentsâ score of IPS subject in experiment class more high than control class. Experiment class gets average grade of 87.08 meanwhile, control class gets average score of 67.78. Hypothesis test is with t test where can be got Tcalculate (2.84) > Ttable (1.67) in order to H0 is rejected and H1 is accepted. In briefly, hypothesis is accepted. This case can be concluded that the different of the studentsâ score use learning model for Question Students Have type with full speak up in IPS (history) lesson at class VII SMPN 17 Padang. Experiment class gets 87.08 score more high than the studentsâ score in control class of 67.78 score. Applying of this strategy will help the students remember and develop their thinking and knowledge from learning model for Question Students Have type in teaching learning process at class.